Cover Picture: Protic and Aprotic Ionic Liquids in Combination with Hard Carbon for Lithium‐Ion and Sodium‐Ion Batteries (Batteries & Supercaps 6/2018). Issue 6 (21st November 2018) - Arnaiz, Maria; Huang, Peihua; Ajuria, Jon; Rojo, Teófilo; Goikolea, Eider; Balducci, Andrea
Abstract : The front cover artwork is provided in collaboration of the Supercapacitors Research Line from CICenergiGUNE and the Institute for Technical Chemistry and Environmental Chemistry and the Center for Energy and Environmental Chemistry Jena (CEEC Jena) of the Friedrich‐Schiller‐University Jena. The Front Cover illustrates a battery based on a combination of an olive pit derived hard carbon with different ionic liquids, studied for both, lithium‐ion and sodium‐ion battery technologies. More Information can be found in the article by M. Arnaiz and co‐workers (DOI:10.1002/batt.201800073 ).